Perancangan Sistem Monitoring Data Order di Pt. Sucofindo Cabang Jambi - Afriyadi, Hery; Hidayat, Taufik; Triandi, Dapit; Zami, Zam; Wulandari, Siti; Nabila, Septi Salsa (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The advancement of information technology demands companies to have efficient information systems, especially in managing order data. PT SUCOFINDO Jambi Branch previously used a manual spreadsheet-based method, which caused difficulties in monitoring order status in real-time. This study aims to design a web-based order monitoring system using ReactJS and Firebase to improve the efficiency of fast and accurate order tracking. Agile methodology is applied in development with a qualitative approach through observation, interviews, and documentation studies. The resulting system facilitates real-time order supervision and accelerates management decision-making. This system is expected to significantly enhance the operations of PT SUCOFINDO Jambi Branch and become an effective solution in order data management.